The American Society for Clinical Pathology's Job Satisfaction, Well-Being, and Burnout Survey of Pathologists. Issue 4 (21st February 2020) - Garcia, Edna; Kundu, Iman; Kelly, Melissa; Soles, Ryan; Mulder, Lotte; Talmon, Geoffrey A
Abstract: Objectives: To examine job satisfaction, well-being, job stress, and burnout among pathologists. Methods: The study utilized a cross-sectional survey design. The survey was administered online via the American Society for Clinical Pathology's (ASCP's) survey tool to elicit information about job satisfaction, well-being, job stress, and burnout among pathologists. Results: Job satisfaction is high and well-being is rated fair to good by most respondents. However, feelings of anxiety or worry about work, high levels of stress, and burnout are prevalent among pathologists. The main contributing factor to job stress, burnout, and work-life balance is quantity of workload. Conclusions: Creating targeted interventions based on the results of this survey may help improve the type and quality of wellness programs for pathologists. Trust among team members, managers and clinicians, and institutions can help reduce stress and increase collaboration, engagement, and motivation.